2016
DOI: 10.12688/f1000research.6358.2
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response and its potential role in Huntington's disease elucidated by a systems biology approach

Abstract: Huntington ś disease (HD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 93 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…To determine if gene transcription underlies the alterations in protein expression, we performed real-time qPCR on samples from R6/2 and WT mice using isoform-specific amplification of Slc12A5 (KCC2) and Slc12A2 (NKCC1). We used previously identified stable control genes for R6/2 mice ( Rpl13a , ATP5b , Ubc , Canx ) ( 41 ) and found a significant decrease in KCC2 mRNA from R6/2 mice (7 wk old) compared with WT, consistent with bioinformatic predictions ( 27 ) ( Fig. 2 F and SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To determine if gene transcription underlies the alterations in protein expression, we performed real-time qPCR on samples from R6/2 and WT mice using isoform-specific amplification of Slc12A5 (KCC2) and Slc12A2 (NKCC1). We used previously identified stable control genes for R6/2 mice ( Rpl13a , ATP5b , Ubc , Canx ) ( 41 ) and found a significant decrease in KCC2 mRNA from R6/2 mice (7 wk old) compared with WT, consistent with bioinformatic predictions ( 27 ) ( Fig. 2 F and SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 77%
“…Recent proteomic studies revealed that the KCC2 encoding gene, Slc12A5 , is highly enriched in Htt proteome ( 25 , 26 ), but despite the strong correlation, this interaction has not been validated. Furthermore, a bioinformatic analysis of the unfolded protein response (UPR)-regulated genes in HD reveals an increase in NKCC1 mRNA and a decrease in KCC2 mRNA ( 27 ), which is significant because UPR is implicated in numerous neurodegenerative diseases including HD ( 28 30 ). Based on the previous data linking (m)Htt and Cl − transporters ( 25 , 26 ) and the important role of inhibition in learning and memory, we hypothesized that KCC2 function is dysregulated in the HD brain, resulting in weakened inhibitory GABAergic transmission, which contributes to the hippocampal-dependent learning and memory deficits that emerge early in HD.…”
mentioning
confidence: 99%
“…Htt-NTFs engage in a wide variety of proteinprotein interactions (75,(81)(82)(83)(84)(85)(86)(87)(88)(89)(90). These "interactomes" are tissue-specific and within a tissue-type, the nodes and edges in an interaction network are known to be different for Htt-NTFs with wild-type versus mutant polyQ lengths (90).…”
Section: Understanding the Effects Of Htt-ntf Binding Partners In Termentioning
confidence: 99%
“…Sorcin is overexpressed in a PD cell model induced by 1-methyl-4-phenylpyridinium ion (MPP + ) in SH-SY5Y cells [53] , which is one of the most differentially expressed proteins in PD vs. normal human substantia nigra [54] and in PD vs. human brain samples [55] , and is overexpressed in AD brain samples [56][57][58] , in particular in sporadic AD [59] and in AD brains with severe cerebral amyloid angiopathy [60] , as well as in frontal cortical tissues from postmortem cases of frontotemporal dementia [61] . Further, Sorcin is overexpressed in 7 different Huntington's disease human and mice models, where it has been associated with the unfolded protein response [62] . Sorcin also interacts with the ionotropic glutamate receptor NMDAR1 Ca 2+ channel, important in several cascade pathways and in synaptic plasticity, in caudate-putamen nucleus [63] , and with annexins A7 and A11, involved in Ca 2+ homeostasis in astrocytes [64] .…”
Section: The Roles Of Sorcin In the Cell: Sorcin Localization Cell Cmentioning
confidence: 99%